Clinical outcomes after cardiac transplantation in muscular dystrophy patients - Wu, Roland S.; Gupta, Sachin; Brown, Robert N.; Yancy, Clyde W.; Wald, Joyce W.; Kaiser, Patricia; Kirklin, Nicole M.; Patel, Parag C.; Markham, David W.; Drazner, Mark H.; Garry, Daniel J.; Mammen, Pradeep P.A. (The Journal of heart and lung transplantation, 2010)
Patients with muscular dystrophy are at risk of developing a dilated cardiomyopathy and can progress to advanced heart failure. At present, it is not known whether such patients can safely undergo cardiac transplantation. This was a retrospective review of the Cardiac Transplant Research Database, a multi-institutional registry of 29 transplant centers in the United States, from the years 1990 to 2005. The post-cardiac transplant outcomes of 29 patients with muscular dystrophy were compared with 275 non-muscular dystrophy patients with non-ischemic cardiomyopathy, matched for age, body mass index, gender, and race. Becker's muscular dystrophy was present in 52% of the patients. Survival in the muscular dystrophy patients was similar to the controls at 1 year (89% vs 91%; p = 0.5) and at 5 years (83% vs 78%; p = 0.5). The differences in rates of cumulative infection, rejection, or allograft vasculopathy between the 2 groups were not significant (p > 0.5 for all comparisons). Recognizing the limitations of the present investigation (ie, selection bias and data lacking in the functional capacity of the muscular dystrophy patients), the current study suggests that the clinical outcomes after cardiac transplantation in selected patients with muscular dystrophy are similar to those seen in age-matched patients with non-ischemic cardiomyopathy.